Mentoring Under Duress: Lessons from the Camino de Santiago and Beyond - John Riofrio "Rio" (Voces y Silencios: Revista Latinoamericana de Educación)
This essay is a first-hand account of a study abroad program I co-led on the Camino de Santiago in May of 2022. It provides an overview of the challenges and hardships associated with mentoring and teaching in an emotionally charged environment like the Camino. The essay argues that the process of mentoring under duress reveals the fault lines that often trouble teachers’ efforts to push, or challenge, their students to move beyond their own perceptions of their limitations. These fault lines are not limited to exceptional contexts like the Camino but rather inhere in pedagogical spaces where students come in with cultural constituted expectations of both the teacher and the subject.